(untitled) (Global Journal of Human-Social Science, 2013)
Producing and consuming electricity are strongly related to macro -economic such as growth, employment and price. However, this relationship in many circumstances, places, times are not in a direction. The relationship of processing electricity and the economy depends on the structure between production and consumption, the cost of structure of sectors in the economy, the use of electricity by the producer, the consumer and internal structure of electricity industry of each country in each time.